Parliamentary practices in Holyrood: ‘new politics’ and the SNP - Fiona Simpkins (Revue LISA)
The Scottish Parliament was meant to represent a revolution in the way that Scots were governed as its supporters frequently expressed the hope that such a body would be a new type of institution that would represent a break with the Westminster model and would offer a new approach to the way that the business of government is carried on. The political arena that emerged out of the blueprint produced by the Scottish Constitutional Convention in the 1990s was the result of a historic consensus and was designed as a more inclusive, representative, transparent and collegial body which was to usher in ‘new politics’ for Scotland. This paper will therefore seek to examine to what extent the Scottish Constitutional Convention’s initial goal of a more open, representative and participative approach to politics has been met and question the impact of its relative success on the surge of nationalism in Scotland.